Influence of Public Procurement and Asset Disposal Act on Performance of Executive State Corporations in Kenya - Omondi Musewe, Stevens; Gekara, Geoffrey (International Journal of Supply Chain and Logistics, 2021)
Purpose: The purpose of the study was to examine influence of public procurement and asset disposal Act on performance of executive state corporations in Kenya with an aim of making recommendations on proper use. Methodology: The study employed a descriptive research design targeting the all 62 executive state corporations operating in Kenya. Data was collected from heads of procurement and their deputies in the entities. The researcher preferred this method because it allowed an in-depth study of the subject. Data was collected using self-administered questionnaires. Structured questionnaires were used to collect data. Data was analyzed using descriptive and inferential statistics. Quantitative data was analyzed using multiple regression analysis. The qualitative data generated was analyzed by use of Statistical Package of Social Sciences (SPSS) version 22. The response rate of the study was 81%. The findings of the study indicated that regulation bodies, methods of procurement, preferences and reservations and disposal of assets have a positive relationship with performance of executive state corporations in Kenya. Results and conclusion: The independent variables reported R value of 0.846 indicating that there was perfect relationship between dependent variable and independent variables. R square value of 0.715 means that 71.5% of the corresponding variation in performance of executive state corporations in Kenya can be explained or predicted by (preferences and reservation, regulation bodies, disposal of assets and methods of procurement) which indicated that the model fitted the study data. The results of regression analysis revealed that there was a significant positive relationship between dependent variable and independent variable at (Î²=0.715), p=0.000 <0.05). The findings of the study indicated that logistics information system, freight management, distributor base rationalization and transport planning have a positive relationship with performance of freight forwarding companies in Kenya. Unique contribution to theory, policy and practice: Finally, the study recommended that public institutions should embrace regulation bodies, methods of procurement, preferences and reservations and disposal of assets so as to improve performance of executive state corporations and further researches should to be carried out in other public institutions to find out if the same results can be obtained.